2007
DOI: 10.1021/la070139o
|View full text |Cite
|
Sign up to set email alerts
|

Improving Hydrophilicity and Protein Resistance of Poly(vinylidene fluoride) Membranes by Blending with Amphiphilic Hyperbranched-Star Polymer

Abstract: To endow hydrophobic poly(vinylidene fluoride) (PVDF) membranes with reliable hydrophilicity and protein resistance, an amphiphilic hyperbranched-star polymer (HPE-g-MPEG) with about 12 hydrophilic arms in each molecule was synthesized by grafting methoxy poly(ethylene glycol) (MPEG) to the hyperbranched polyester (HPE) molecule using terephthaloyl chloride (TPC) as the coupling agent and blended with PVDF to fabricate porous membranes via phase inversion process. The chemical composition changes of the membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
148
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(155 citation statements)
references
References 54 publications
7
148
0
Order By: Relevance
“…Their results demonstrated that the antifouling property of the membrane was improved greatly, whereas the membrane structure was little affected. Since then, many amphiphilic copolymers, such as tri-block, 49 comb-like 50 and branched copolymers, 51 have been used as additives to blend with host polymers to produce composite membranes with enhanced antifouling properties. Among these copolymers, ternary copolymers containing a hydrophobic 'anchoring' segment, hydrophilic fouling resistance segment or nonpolar hydrophobic segment with low surface free energy have received much attention because of their excellent complicated structure.…”
Section: Blendingmentioning
confidence: 99%
“…Their results demonstrated that the antifouling property of the membrane was improved greatly, whereas the membrane structure was little affected. Since then, many amphiphilic copolymers, such as tri-block, 49 comb-like 50 and branched copolymers, 51 have been used as additives to blend with host polymers to produce composite membranes with enhanced antifouling properties. Among these copolymers, ternary copolymers containing a hydrophobic 'anchoring' segment, hydrophilic fouling resistance segment or nonpolar hydrophobic segment with low surface free energy have received much attention because of their excellent complicated structure.…”
Section: Blendingmentioning
confidence: 99%
“…48 Protein Adsorption onto Membranes Membrane fouling can be caused by various undesired interactions, such as electrostatic attraction, van der Waals interactions, and hydrogen bonding, between the membrane materials and typical colloids (e.g., proteins or oil droplets in water). 49,50 Here, we examined the antifouling properties of the PES membranes using static protein adsorption experiments with BSA and LYS as model proteins. The adsorbed amounts of BSA and LYS for virgin and modified PES membranes are presented in Figure 9.…”
Section: Mechanical Strength Measurementmentioning
confidence: 99%
“…The nonspecifically adsorbed proteins, as well as the adherence of microorganisms are known to induce adverse biological responses which interfere with medical device function, as is often the case with contact and intraocular lenses, blood contacting devices, bacteria-resistant implants and surgical tools [1][2][3][4][5][6][7][8][9][10][11][12]. Therefore, the prevention of such the protein adsorptions and the bacterial adherence are the major issues for successful implantation of biomaterials.…”
Section: Introductionmentioning
confidence: 99%